PENERAPAN STRATEGI KWL (KNOW, WANT TO KNOW, LEARNED) UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK PESERTA DIDIK KELAS III DI SD NEGERI 12 KOTO BARU KECAMATAN KUBUNG KABUPATEN SOLOK - reni guswita (Jurnal Tunas Pendidikan, 2019)
The result of observation in the field had indicated that the thematic learning process conducted by the teacher had not yet been able to improve the students’ learning achievement. To deal with this problem, Know Want to Know Learned (KWL) strategy was applied. This research was designed for describing the implementation of KWL strategy in pre-activity, whilst-activity and post-activity to improve the third grade students’ thematic learning achievement at SD Negeri 12 Koto Baru Kecamatan Kubung Kabupaten Solok. This was a Classroom Action research which was conducted in two cycles. Each cycle consisted of four phases including planning, acting, observing and reflecting. The subject of the research was 30 students in the third grade. The data was gotten by using observation sheet, note-field and test. The data gotten was analyzed qualitatively and quantitatively. Based on the results of the research it was revealed that from the first cycle to the second one, the score of the teacher’s activities improved from 75% into 88,75%, the students’ activities improved from 65 into 81,75, and the students’ learning achievement improved from 70,2 into 80,8.